2014
DOI: 10.1016/j.nlm.2014.06.012
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of MDMA on olfactory memory and reversal learning in rats

Abstract: The effects of acute and sub-chronic MDMA were assessed using a procedure designed to test rodent working memory capacity: the odor span task (OST). Rats were trained to select an odor that they had not previously encountered within the current session, and the number of odors to remember was incremented up to 24 during the course of each session. In order to separate drug effects on the OST from more general performance impairment, a simple olfactory discrimination was also assessed in each session. In Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…These results closely parallel the present findings with multiple stimuli to remember in the OST—generally impairment that was task-independent and often occurred at relatively low doses was found. These findings were also quite similar to a previous study from our laboratory which found that MDMA also produced only nonselective impairment of responding with the OST/SDC procedure (Hawkey, April, & Galizio, 2014). Although none of the rats showed increased accuracy after either methamphetamine or methylphenidate, it must be noted that baseline levels were high in both tasks and it is possible that a ceiling effect may have obscured observation of enhancement.…”
Section: Discussionsupporting
confidence: 91%
“…These results closely parallel the present findings with multiple stimuli to remember in the OST—generally impairment that was task-independent and often occurred at relatively low doses was found. These findings were also quite similar to a previous study from our laboratory which found that MDMA also produced only nonselective impairment of responding with the OST/SDC procedure (Hawkey, April, & Galizio, 2014). Although none of the rats showed increased accuracy after either methamphetamine or methylphenidate, it must be noted that baseline levels were high in both tasks and it is possible that a ceiling effect may have obscured observation of enhancement.…”
Section: Discussionsupporting
confidence: 91%
“…Doses of 0. 1, 0.3, 0.32, 0.75, 1.0, 1.25, 1.7, 1.75, 1.8, 2.0, and 2.25 mg/kg produced no effects on working memory when animals were tested on-drug on the DMS (LeSage et al, 1993;Frederick et al, 1995a,b;Harper et al, 2005), OST (Hawkey et al, 2014), DA (Young et al, 2005), RAM (Braida et al, 2002;Kay et al, 2010), or MWM (Galizio et al, 2014) tasks. Doses of 0.3, 0.75, 1.0, 1.25, 1.7, and 2.25 mg/kg produced no effects on spatial learning and memory when animals were tested on-drug on the MWM (Galizio et al, 2014), RAM (Kay et al, 2010), or SD (Young et al, 2005) tasks.…”
Section: B Findings By Dosementioning
confidence: 99%
“…For example, both scopolamine and MDMA produced dose-dependent decreases in OST accuracy and span length, but significant impairment was only noted at doses that also impaired simple discrimination accuracy (Galizio et al, 2013; Hawkey et al, 2014). Thus, neither drug appeared to act in any selective fashion on within session remembering or to affect the number of stimuli rats could remember.…”
Section: Control By Multiple Stimuli: the Odor Span Taskmentioning
confidence: 99%